2012
DOI: 10.1002/anie.201204964
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease, Cholesterol, and Statins: The Junctions of Important Metabolic Pathways

Abstract: Recent years have seen a significant increase in published data supporting the positive effects of statins on neurodegenerative diseases, in particular on Alzheimer's disease. Statins show neuroprotective activity by a combination of different cellular and systemic mechanisms that are based on the inhibition of the biosynthesis of cholesterol and isoprenoid by-products. The promising results obtained in vivo and in epidemiological studies are generally not in accordance with those of placebo-controlled randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 93 publications
0
38
0
2
Order By: Relevance
“…Los radicales libres y las especies reactivas del oxígeno que se generan en el organismo son neutralizados normalmente por moléculas endó-genas 33 , sin embargo, este balance antioxidante se altera en patologías relacionadas con la edad 40 , como la EA, favoreciendo una mayor producción de especies oxidativas las cuales se asocian con daño neuronal 32 , peroxidación lipídica y oxidación de enzimas relacionadas con la mantención de funciones de las neuronas y la glia 41 .…”
Section: Dieta Mediterránea Y Estrés Oxidativounclassified
See 1 more Smart Citation
“…Los radicales libres y las especies reactivas del oxígeno que se generan en el organismo son neutralizados normalmente por moléculas endó-genas 33 , sin embargo, este balance antioxidante se altera en patologías relacionadas con la edad 40 , como la EA, favoreciendo una mayor producción de especies oxidativas las cuales se asocian con daño neuronal 32 , peroxidación lipídica y oxidación de enzimas relacionadas con la mantención de funciones de las neuronas y la glia 41 .…”
Section: Dieta Mediterránea Y Estrés Oxidativounclassified
“…Junto con ello, este péptido es capaz de inhibir la cadena respiratoria, promoviendo disfunción mitocondrial y disminución de los niveles de ATP, desestabilizando los mecanismos de defensa antioxidante 40 .…”
Section: Dieta Mediterránea Y Estrés Oxidativounclassified
“…Cholesterol is the main sterol in animal tissues, and has very important functions, as being a major component of eukaryotic membranes, and function as a biosynthetic precursor of important bioactive molecules such as steroid hormones and bile acids [83]. And also it has been shown that cholesterol can directly modulate the processing of APP [84,85].…”
Section: Effects Of High Cholesterol Diet On App Processingmentioning
confidence: 99%
“…Accordingly, it has been reported that, increased cholesterol levels enhance β and γ-secretase activity therefore, promoting APP metabolism by the amyloidogenic pathway. Conversely a decrease in intracellular cholesterol, leads to structural rupture of the lipid rafts, favoring α-secretase non-amyloidogenic APP cleavage, leading to a significant decrease in Aβ levels [83].…”
Section: Effects Of High Cholesterol Diet On App Processingmentioning
confidence: 99%
See 1 more Smart Citation